Porous carbon, silicon carbon negative electrode material, preparation method, pole piece and battery
By doping carbon nanotubes into the carbon skeleton and ionic thermal reactions with ionic liquids, porous carbon materials with high mechanical and electrochemical properties were prepared, which solved the problem of low strength and easy powder removal of existing porous carbon materials.
Patent Information
- Application Number
- CN202510148282.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-25
AI Technical Summary
The strength of existing porous carbon materials is not high and are prone to powder and fall off in actual applications, which limits its application prospects.
By doping carbon nanotubes into the carbon skeleton and performing ionic thermal reactions under the action of ionic liquid, porous carbon materials with rich pore structures are prepared to improve their mechanical and electrochemical properties.
The mechanical and electrochemical properties of porous carbon materials have been improved, and its stability and performance in negative electrode materials applications have been improved.
Smart Images

Figure CN119890270A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous carbon, silicon-carbon negative electrode material, a preparation method, a pole piece and a battery. Background Art
[0002] As existing traditional energy (such as oil, coal resources, etc.) is non-renewable and energy consumption is increasing, new energy sources are being sought. The development of batteries has become an indispensable source of power. Lithium batteries with high energy density and high specific power meet the needs of electronic devices, so it is necessary to explore new high-capacity negative electrode materials.
[0003] Porous carbon materials have broad application prospects in the field of energy storage and conversion due to their high specific surface area, good conductivity and high capacity. Patent application CN115554982A provides a method for preparing carbon materials, comprising the following steps: mixing polymerization monomers, water, catalysts, additives and ionic liquid templates, conducting a hydrothermal reaction to obtain an organic wet gel; drying the organic wet gel to obtain an organic dry gel; mixing the organic dry gel with a strong base, and carbonizing it in an ammonia atmosphere to obtain a carbon material. However, this technology is limited by its precursor and hydrothermal carbonization process, resulting in low strength of porous carbon and limitations in practical applications, such as the problem that silicon-carbon materials are easy to pulverize and fall off, indicating that this technology still needs to be improved. Summary of the invention
[0004] The present invention provides a porous carbon, silicon-carbon negative electrode material, preparation method, pole piece and battery to solve the defects in the prior art. The present invention uses carbon nanotubes as a reinforcing phase to prepare a porous carbon material with a rich pore structure, thereby improving its mechanical properties and electrochemical properties.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a porous carbon comprising a carbon skeleton and pores distributed on the carbon skeleton, wherein the carbon skeleton comprises amorphous carbon and carbon nanotubes, wherein the amorphous carbon is doped with nitrogen, fluorine and boron elements; and the mass ratio of the amorphous carbon to the carbon nanotubes is (1-3): 1.
[0007] In the present invention, the amorphous carbon may be doped with sulfur, wherein nitrogen diffuses into carbon interlayers or defects of carbon nanotubes in the form of graphitic nitrogen or pyridinic nitrogen, and sulfur, fluorine and boron directly combine with carbon atoms to form sulfur-carbon bonds, fluorine-carbon bonds or boron-carbon bonds.
[0008] In the present invention, the diameter of the carbon nanotubes may be 1-2 nm.
[0009] In the present invention, the length of the carbon nanotubes may be 0.5-30 μm.
[0010] Preferably, the length of the carbon nanotubes is 0.5-2 μm.
[0011] Preferably, the length of the carbon nanotubes is 5-30 μm.
[0012] In the present invention, the carbon nanotubes may be single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0013] Preferably, the carbon nanotubes are single-walled carbon nanotubes and multi-walled carbon nanotubes, and the mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is (1-6): (1-4), for example, 1:1, 3:1 or 1:3.
[0014] In the present invention, the specific surface area of the porous carbon can be 300-900 m 2 / g, preferably 520-900 m 2 / g, for example, 350 m 2 / g, 420 m 2 / g, 430 m 2 / g, 480 m 2 / g, 524 m 2 / g, 573 m 2 / g, 580 m 2 / g, 632 m 2 / g, 695m 2 / g, 755 m 2 / g, 786 m 2 / g, 790 m 2 / g, 794 m 2 / g, 802 m 2 / g, 815 m 2 / g, 823 m 2 / g, 825 m 2 / g, 832m 2 / g or 856 m 2 / g.
[0015] In the present invention, the pore volume of the porous carbon can be 0.4-0.8 cm 3 / g, preferably 0.55-0.8 cm 3 / g, for example 0.47 cm 3 / g, 0.53 cm 3 / g, 0.54 cm 3 / g, 0.55 cm 3 / g, 0.56 cm 3 / g, 0.57 cm 3 / g, 0.59 cm 3 / g, 0.62 cm 3 / g, 0.64 cm 3 / g, 0.65 cm 3 / g, 0.67 cm 3 / g, 0.68 cm 3 / g, 0.7 cm 3 / g, 0.71 cm 3 / g, 0.72 cm 3 / g or 0.75 cm 3 / g.
[0016] In the present invention, the micropore ratio of the porous carbon may be 40%-75%, preferably 53%-75%, such as 40.23%, 48.52%, 49.63%, 52.67%, 54.73%, 56.42%, 56.58%, 57.49%, 62.87%, 64.52%, 67.52%, 67.63%, 67.72%, 67.85%, 68.23%, 68.57%, 68.75%, 68.98% or 71.89%. The micropore ratio refers to the percentage of the pore volume with a pore size of ≤2 nm in the porous carbon material to the total pore volume.
[0017] In the present invention, the average pore size of the porous carbon may be 1.75-1.85 nm, for example, 1.7713 nm, 1.7781 nm, 1.7808 nm, 1.7816 nm, 1.782 nm, 1.7832 nm, 1.7845 nm, 1.786 nm, 1.7908 nm, 1.7912 nm, 1.7965 nm, 1.7992 nm, 1.8012 nm, 1.802 nm, 1.8027 nm, 1.8107 nm, 1.8161 nm, 1.8171 nm or 1.8313 nm.
[0018] In the present invention, the tap density of the porous carbon can be 0.36-0.45 g / cm 3 , preferably 0.36-0.425 g / cm 3 , for example 0.374 g / cm 3 , 0.381 g / cm 3 , 0.384 g / cm 3 , 0.385 g / cm 3 , 0.386 g / cm 3 , 0.387 g / cm 3 , 0.401 g / cm 3 , 0.402 g / cm 3 , 0.407 g / cm3 , 0.41 g / cm 3 , 0.413 g / cm 3 , 0.416 g / cm 3 , 0.426 g / cm 3 , 0.428 g / cm 3 , 0.43 g / cm 3 , 0.435 g / cm 3 or 0.439 g / cm 3 .
[0019] In a second aspect, the present invention provides a method for preparing porous carbon, which comprises the following steps:
[0020] S1. subjecting a precursor solution to an ionothermal reaction to obtain an ion gel; the precursor solution comprises carbon nanotubes, an ionic liquid, a carbon precursor and a crosslinking agent, the viscosity of the ionic liquid is 0.03-0.35 Pa·s, and the mass ratio of the carbon nanotubes, the ionic liquid, the carbon precursor and the crosslinking agent is (5-10): (25-40): (2-5): (0.2-0.5);
[0021] S2, freeze-drying the ion gel to obtain a freeze-dried gel;
[0022] S3, carbonizing the freeze-dried gel.
[0023] In the present invention, in step S1, the diameter of the carbon nanotubes may be 1-2 nm.
[0024] In the present invention, in step S1, the length of the carbon nanotubes may be 0.5-30 μm.
[0025] Preferably, the length of the carbon nanotubes is 0.5-2 μm.
[0026] Preferably, the length of the carbon nanotubes is 5-30 μm.
[0027] In the present invention, in step S1, the carbon nanotubes may be single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0028] Preferably, the carbon nanotubes are single-walled carbon nanotubes and multi-walled carbon nanotubes, and the mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is (1-6): (1-4), for example, 1:1, 3:1 or 1:3.
[0029] In the present invention, in step S1, the carbon nanotubes may be modified with carboxyl groups.
[0030] Preferably, the carboxyl content of the carbon nanotubes may be greater than 2 wt %, for example, 2.73 wt %.
[0031] In the present invention, in step S1, the viscosity of the ionic liquid is preferably 0.03-0.25 Pa·s, for example, 0.039 Pa·s, 0.118 Pa·s, 0.14 Pa·s, 0.202 Pa·s or 0.341 Pa·s. The viscosity is measured by an Ubbelohde viscometer at 25°C and 1 atm.
[0032] In the present invention, in step S1, the ionic liquid may be an imidazole ionic liquid, such as [EMIM]BF 4 (0.039Pa·s), [HMIM]BF 4 (0.202 Pa·s), [C 7 MIM]BF 4 (0.118 Pa·s), [OMIM] BF 4 (0.341 Pa·s) or [BMIM]BF 4 (0.140 Pa·s). The viscosity is measured by an Ubbelohde viscometer at 25°C and 1 atm.
[0033] In the present invention, in step S1, the carbon precursor is conventionally selected in the art, such as polyvinyl alcohol (PVA).
[0034] In the present invention, in step S1, the precursor solution may further include a surfactant. The surfactant is conventionally selected in the art, such as sodium dodecyl sulfate (SDS). The mass ratio of the carbon nanotubes to the surfactant may be (0.2-0.3): 0.1, such as 0.2: 0.1, 0.25: 0.1 or 0.3: 0.1.
[0035] In the present invention, in step S1, the cross-linking agent is conventionally selected in the art, such as glutaraldehyde.
[0036] In the present invention, in step S1, the mass ratio of the carbon nanotubes to the ionic liquid may be (0.2-0.3):0.8, for example, 0.2:0.8, 0.25:0.8 or 0.3:0.8.
[0037] In the present invention, in step S1, the mass ratio of the carbon nanotubes to the carbon precursor may be (0.2-0.3):0.07, for example, 0.2:0.07, 0.25:0.07 or 0.3:0.07.
[0038] In the present invention, in step S1, the mass ratio of the carbon nanotubes to the cross-linking agent may be (0.2-0.3):0.01, for example, 0.2:0.01, 0.25:0.01 or 0.3:0.01.
[0039] In the present invention, in step S1, the carbon nanotubes may be first mixed with the ionic liquid. During the mixing, stirring or ultrasound may be used. The stirring speed is conventionally selected in the art, such as 300-800 rpm. The stirring time is conventionally selected in the art, such as 30-90 min. The ultrasound frequency is conventionally selected in the art, such as 20 kHz. The ultrasound power is conventionally selected in the art, such as 500 W. The ultrasound time is conventionally selected in the art, such as 30 min.
[0040] In the present invention, in step S1, the temperature of the ion thermal reaction is conventionally selected in the art, preferably 150-350°C, such as 250°C.
[0041] In the present invention, in step S1, the time of the ion thermal reaction is conventionally selected in the art, preferably 2-24 hours, for example 8 hours.
[0042] In the present invention, in step S2, the freeze-drying temperature is conventionally selected in the art, preferably -80 to -20°C, such as -80°C, -50°C or -20°C.
[0043] In the present invention, in step S2, the freeze-drying time is conventionally selected in the art, preferably 2-10 h.
[0044] In the present invention, in step S3, the atmosphere of the carbonization treatment is a protective gas, which refers to a gas that does not react with the raw material, such as nitrogen or an inert gas. The flow rate of the protective gas is conventionally selected in the art, such as 3 L / min.
[0045] In the present invention, in step S3, the terminal temperature of the carbonization treatment may be 600-1000°C, preferably 700-1000°C, such as 600°C, 700°C, 800°C, 900°C or 1000°C.
[0046] In the present invention, in step S3, the carbonization treatment time can be 0.5-2.5 h, preferably 1-2 h, such as 0.5 h, 1 h, 1.5 h, 2 h or 2.5 h. The carbonization treatment time refers to the time maintained after reaching the end temperature, and the heating time is not included.
[0047] In a specific embodiment of the present invention, in step S3, the carbonization treatment is: in a nitrogen atmosphere, the heating rate is set to increase the temperature to 400°C at 2°C / min, then increase the temperature to 600°C at 1°C / min, and then increase the temperature to 800°C at 2°C / min, and carbonize for 1 h.
[0048] In a third aspect, the present invention provides porous carbon prepared by the method for preparing porous carbon as described above.
[0049] In a fourth aspect, the present invention provides a silicon-carbon negative electrode material, which includes the porous carbon as described above, silicon particles distributed in the pores of the porous carbon, and a carbon layer coated on the surface of the porous carbon; based on the total mass of the silicon-carbon negative electrode material, the mass of the porous carbon accounts for 40-70%, the mass of the silicon particles accounts for 10-30%, and the mass of the carbon layer accounts for 0.5-10%.
[0050] In a fifth aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0051] Step 1, in a protective atmosphere, at 300-400° C., passing a silicon source gas through the porous carbon as described above to obtain a composite material;
[0052] Step 2: Passing a carbon source gas through the composite material at 600-700° C. under a protective atmosphere.
[0053] In the present invention, the protective atmosphere refers to a gas that does not participate in the reaction, such as nitrogen or an inert gas.
[0054] In the present invention, in step 1, the silicon source gas may be SiH 4 .
[0055] In the present invention, in step 1, the flow rate of the silicon source gas can be 5-10 mL / min.
[0056] In the present invention, in step 1, the silicon source gas may be introduced for 30-60 minutes.
[0057] In the present invention, in step 1, the porous carbon can be rotated at a speed of 5-10 rpm.
[0058] In the present invention, in step 1, the vacuum degree of the protective atmosphere may be 10-50 Pa, for example, 20 Pa.
[0059] In the present invention, in step 1, the equipment used may be a tube furnace. The tube furnace is provided with a rotating mechanism.
[0060] In the present invention, in step 2, the carbon source gas may be acetylene.
[0061] In the present invention, in step 2, the amount of the carbon source gas introduced can be 2-5 mL / min.
[0062] In the present invention, in step 2, the carbon source gas may be introduced for 60-120 min.
[0063] In the present invention, in step 2, the porous carbon can be rotated at a speed of 5-10 rpm.
[0064] In the present invention, in step 2, the equipment used may be a tube furnace. The tube furnace is provided with a rotating mechanism.
[0065] In a sixth aspect, the present invention provides a silicon-carbon negative electrode material obtained by the method for preparing the silicon-carbon negative electrode material as described above.
[0066] In a seventh aspect, the present invention provides a pole piece, which includes a coating layer and a current collector, wherein the coating layer includes the silicon-carbon negative electrode material as described above.
[0067] In an eighth aspect, the present invention provides a battery comprising the pole piece as described above.
[0068] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0069] The reagents and raw materials used in the present invention are commercially available.
[0070] The positive and progressive effects of the present invention are:
[0071] (1) The porous carbon of the present invention uses ionic liquid as solvent and / or template agent and carbon nanotubes as reinforcing phase, which is conducive to preparing porous carbon with high specific surface area and rich pore structure, and improving its mechanical properties and conductivity;
[0072] (2) In the porous carbon of the present invention, the ionic liquid not only provides a carbon source but also provides a nitrogen source, a fluorine source, a sulfur source or a boron source, which can promote the increase of the specific surface area and the formation of micropores and mesopores;
[0073] (3) In the method for preparing porous carbon of the present invention, the ionic liquid can play the dual role of solvent and template during the ionothermal reaction. The process is simple, low-cost, green and environmentally friendly, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 is a flow chart of the preparation of porous carbon in Example 1;
[0075] Figure 2 This is a SEM characterization image of the porous carbon prepared in Example 1;
[0076] Figure 3 N is the porous carbon prepared in Example 1 2 Adsorption–desorption isotherms. DETAILED DESCRIPTION
[0077] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0078] In the following examples and comparative examples, the raw materials used are as follows:
[0079] Single-walled carbon nanotubes, carboxylated, diameter 1-2 nm, length 0.5-2 μm, purity >90%, -COOH content 2.73wt%.
[0080] Multi-walled carbon nanotubes, diameter 1-2 nm, length 5-30 μm, purity 98%.
[0081] PVA, purchased from Maclean, Mw 13000-23000.
[0082] Example 1
[0083] A porous carbon, silicon-carbon negative electrode material and a preparation method thereof, such as Figure 1 , the specific process is as follows:
[0084] (1) Add 0.1 g of single-walled carbon nanotubes and 0.1 g of multi-walled carbon nanotubes to 0.8 g of ionic liquid template [BMIM]BF 4 0.1 g sodium dodecyl sulfate (SDS) was added to the mixture and ultrasonically dispersed for 30 min to obtain a uniform dispersion. 0.07 g PVA was dissolved in 1 ml deionized water under heating and stirring at 80°C in a water bath. The dispersion was mixed with the PVA aqueous solution, and the mechanical stirring speed was set to 500 rpm for 30 min.
[0085] (2) The mixed solution was transferred to an oil bath, and 0.01 g of glutaraldehyde was added to perform an ion thermal reaction at 250 °C for 8 h. After the reaction was completed, the mixture was cooled to room temperature.
[0086] (3) The product was freeze-dried at -80°C for 10 h to obtain a freeze-dried gel with a three-dimensional porous structure;
[0087] (4) The freeze-dried gel was placed in a tubular furnace, and under a nitrogen atmosphere, the heating rate was set to 2°C / min to 400°C, 1°C / min to 600°C, and 2°C / min to 800°C, and the carbonization time was 1 h to obtain porous carbon. The porous carbon includes a carbon skeleton and pores distributed on the carbon skeleton, and the carbon skeleton includes amorphous carbon and carbon nanotubes, and the mass ratio of amorphous carbon to carbon nanotubes is 2.75:1.
[0088] like Figure 2In the figure, the red circle part is micropores, the yellow circle part is mesopores, and the green circle part is macropores; after doping with nitrogen, fluorine and boron elements, nitrogen diffuses into the carbon layers or defects of carbon nanotubes in the form of graphitic nitrogen or pyridine nitrogen, and sulfur, fluorine and boron directly combine with carbon atoms to form sulfur-carbon bonds, fluorine-carbon bonds or boron-carbon bonds.
[0089] After testing, such as Figure 3 , showing a type I isotherm, at extremely low relative pressure (P / P 0 <0.05) and then tends to be flat. This type of isotherm indicates that the material is mainly composed of micropores and has a high specific surface area. The specific surface area of the porous carbon material is 856 m 2 / g, pore volume is 0.75 cm 3 / g;
[0090] (5) The porous carbon material is placed in a tube furnace. Under an argon atmosphere, silane gas is used as the silicon source. The flow rate is precisely controlled by a flow controller. Silane gas is slowly introduced at a flow rate of 10 mL / min for 60 min, so that silane is decomposed at high temperature and deposited in the porous carbon material. The temperature of the tube furnace is controlled at 400°C, and silicon atoms account for 10% of the total mass of the final silicon-carbon negative electrode material. During the silicon deposition process, in order to ensure uniform deposition of silicon, the rotating device of the tube furnace can be properly turned on to allow the sample to slowly rotate in the furnace, and the speed is controlled at 10 rpm. At the same time, by adjusting the vacuum degree of the tube furnace within the range of 20 Pa, it is helpful for silane gas to better penetrate into the porous carbon material and achieve uniform deposition. Acetylene is used as the carbon source for carbon coating. After the silicon deposition is completed, the temperature of the tube furnace is raised to 600°C, the argon atmosphere is maintained (the flow rate remains unchanged), and acetylene gas is introduced at a flow rate of 5 mL / min for 120 min. The amount of acetylene introduced is based on the formation of a dense carbon layer on the surface of the material. The carbon layer accounts for about 5% of the total mass of the final silicon-carbon negative electrode material. It is generally fine-tuned based on experience and subsequent characterization results. The tubular furnace rotating device is also turned on, and the speed is maintained at 10 rpm to ensure the uniformity of the carbon coating. After the reaction is completed, the temperature is naturally cooled to room temperature, and the sample is taken out under argon protection to obtain a silicon-carbon composite porous carbon material.
[0091] Example 2
[0092] The only difference from Example 1 is that the ionic liquid template is changed to [HMIM]BF 4 .
[0093] Example 3
[0094] The only difference from Example 1 is that the ionic liquid template is changed to [C 7 MIM]BF 4 .
[0095] Example 4
[0096] The only difference from Example 1 is that the ionic liquid template is changed to [OMIM]BF 4 .
[0097] Example 5
[0098] The only difference from Example 1 is that the ionic liquid template is changed to [BMIM]BF 4 .
[0099] Example 6
[0100] The difference from Example 1 is that the carbon nanotubes are only 0.2 g of multi-walled carbon nanotubes.
[0101] Example 7
[0102] The difference from Example 1 is that the carbon nanotubes are only 0.2 g of single-walled carbon nanotubes.
[0103] Example 8
[0104] The only difference from Example 1 is that the mass of the single-walled carbon nanotubes is changed to 0.15 g.
[0105] Example 9
[0106] The only difference from Example 1 is that the mass of the single-walled carbon nanotubes is changed to 0.05 g.
[0107] Example 10
[0108] The only difference from Example 1 is that the mass of the single-walled carbon nanotubes is changed to 0.25 g. The mass ratio of amorphous carbon to carbon nanotubes is 2.2:1.
[0109] Embodiment 11
[0110] The only difference from Example 1 is that the mass of the single-walled carbon nanotubes is changed to 0.3 g. The mass ratio of amorphous carbon to carbon nanotubes is 1.83:1.
[0111] Example 12
[0112] The only difference from Example 1 is that the carbonization end point temperature is changed to 600°C.
[0113] Embodiment 13
[0114] The only difference from Example 1 is that the carbonization end point temperature is changed to 700°C.
[0115] Embodiment 14
[0116] The only difference from Example 1 is that the carbonization end point temperature is changed to 900°C.
[0117] Embodiment 15
[0118] The only difference from Example 1 is that the carbonization end point temperature is changed to 1000°C.
[0119] Example 16
[0120] The only difference from Example 1 is that the carbonization time is changed to 0.5 h.
[0121] Embodiment 17
[0122] The only difference from Example 1 is that the carbonization time is changed to 1.5 h.
[0123] Embodiment 18
[0124] The only difference from Example 1 is that the carbonization time is changed to 2 h.
[0125] Embodiment 19
[0126] The only difference from Example 1 is that the carbonization time is changed to 2.5 h.
[0127] The main experimental conditions in each embodiment are shown in the following table.
[0128]
[0129] Effect Example 1: Microscopic Characteristics of Porous Carbon
[0130] 1. Test object: porous carbon prepared in Examples 1-19.
[0131] 2. Test method:
[0132] (1) The specific surface area, average pore diameter and pore volume were tested by nitrogen adsorption and desorption, which is commonly used in the field;
[0133] (2) Micropore ratio: refers to the percentage of pore volume with pore diameter ≤ 2 nm in the porous carbon material to the total pore volume;
[0134] (3) Tap density: The tap density of a material is measured by a Quantachrome tap density meter. It refers to the mass per unit volume of the powder in a specified container after being tapped.
[0135] 3. Test results: see the table below.
[0136]
[0137] From the comparison of Examples 1-5, it can be seen that the specific surface area, pore volume, micropore ratio, average pore size and tap density of the materials of different types and viscosities of ionic liquids are different. Among them, the porous carbon obtained by the ionic liquid with low viscosity often has a high specific surface area and pore volume, and the micropore ratio is also large. The tap density of porous carbon materials prepared by different ionic liquid types is different, but in general, the tap density is high, indicating that the material has better mechanical strength and usually has better electrical conductivity and electrochemical properties.
[0138] From the comparison of Examples 1, 6-11, it can be seen that the single-walled carbon nanotubes are easier to disperse evenly due to their carboxylation and short length, and the single-walled carbon nanotubes have a high specific surface area, excellent mechanical properties and high electrical conductivity, which significantly improves the specific surface area and pore volume of the material, as well as a higher tap density. As the content of single-walled carbon nanotubes gradually increases, the specific surface area and pore volume first increase and then rapidly decrease.
[0139] From the comparison of Examples 1, 12-19, it can be seen that with the increase of carbonization temperature, the pore volume of the specific surface area of the material gradually increases. When the carbonization temperature is 800°C, it reaches the maximum value, the micropores account for a large proportion, and the porosity is large. However, when the carbonization temperature is further increased, the micropore porosity decreases, and the proportion of mesopores and macropores gradually increases, so that the average pore size increases. With the increase of carbonization time, the specific surface area and pore volume also show a trend of first increasing rapidly, then starting to decline after reaching a peak, and finally significantly decreasing under a long carbonization time.
[0140] Effect Example 2: Electrochemical Performance of Silicon Carbon Anode Materials
[0141] 1. Test object: silicon-carbon negative electrode materials prepared in Examples 1, 5, 6, 9, 12, 15 and 19.
[0142] 2. Test method:
[0143] (1) Half-cell assembly: First, the silicon-carbon negative electrode material is repeatedly washed with deionized water and ethanol and dried to remove impurities. Then, the silicon-carbon negative electrode material, conductive carbon black, carboxymethyl cellulose CMC and binder SBR are mixed in a mass ratio of 95: 1: 2: 2, stirred in N-methylpyrrolidone to form a uniform slurry, and then the slurry is evenly coated on the copper foil using a coater. The coating thickness is controlled to be about 60 μm, and then dried at 80-120 °C for 12 h to ensure that all solvents are evaporated; the dried electrode is rolled to reduce the thickness of the electrode and increase the density, and cut according to the size of the battery shell. CR2032 button batteries are used, and the electrode size is cut according to the size of the button batteries. The diameter is 20 mm. The electrodes, polypropylene separator (thickness 10 μm) and lithium sheet were installed in sequence, and 0.5 ml of electrolyte (volume ratio of ethylene carbonate (EC) 20%, polycarbonate (PC) 20%, diethyl carbonate (DEC) 20%, polypropylene (PP) 15%, LiPF 6 15%, fluoroethylene carbonate (FEC) 6%, polystyrene (PS) 2.5%, LiODFB 1.5%), place the sealing ring and spring, and perform electrochemical testing after sealing.
[0144] (2) Electrochemical performance test: The discharge capacity and first discharge efficiency of the assembled battery were measured under the conditions of charge and discharge voltage ranging from 0.005 V to 1.0 V and charge and discharge rate of 0.1 C according to the conventional test methods in the art.
[0145] Long-term capacity retention rate test: The material was subjected to constant current charge and discharge test using the Blue Electric test system. The voltage test range was 0.01-1.5 V. A small current (0.05 C) was used for activation in the first three cycles, followed by a long cycle test at 0.1 C.
[0146] The test system used in the electrochemical performance test was purchased from Wuhan Blue Electric Electronics Co., Ltd., model CT2001A, and factory number 20170512000.
[0147] 3. Test results: see the table below.
[0148]
[0149] Compared with Example 5, the ionic liquid [EMIM] BF used in Example 1 4The prepared material has high capacity and efficiency, but the capacity retention rate decreases after 100 and 200 cycles. By comparing Examples 12 and 15, it can be found that if the carbonization temperature is too high or too low, the specific surface area and pore volume will be smaller, and the capacity and efficiency of the material will be low. In Example 12, due to the small number of pore structures and the small proportion of micropores, the capacity, efficiency and capacity retention rate are slightly reduced.
[0150] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A porous carbon, characterized in that It includes a carbon skeleton and pores distributed on the carbon skeleton, the carbon skeleton includes amorphous carbon and carbon nanotubes, the amorphous carbon is doped with nitrogen, fluorine and boron elements; the mass ratio of the amorphous carbon to the carbon nanotubes is (1-3):
1.
2. The porous carbon according to claim 1, characterized in that It meets at least one of the following conditions: (1) The amorphous carbon is also doped with sulfur; (2) The diameter of the carbon nanotubes is 1-2 nm; (3) The length of the carbon nanotube is 0.5-30 μm; preferably, the length of the carbon nanotube is 0.5-2 μm; preferably, the length of the carbon nanotube is 5-30 μm; (4) The carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes; preferably, the carbon nanotubes are single-walled carbon nanotubes and multi-walled carbon nanotubes, and the mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is (1-6): (1-4), for example, 1:1, 3:1 or 1:3; (5) The specific surface area of the porous carbon is 300-900 m 2 / g, preferably 520-900 m 2 / g, for example, 350 m 2 / g, 420 m 2 / g, 430 m 2 / g, 480 m 2 / g, 524 m 2 / g, 573 m 2 / g, 580 m 2 / g, 632 m 2 / g, 695 m 2 / g, 755 m 2 / g, 786 m 2 / g, 790 m 2 / g, 794 m 2 / g, 802 m 2 / g, 815 m 2 / g, 823 m 2 / g, 825 m 2 / g, 832 m 2 / g or 856m 2 / g; (6) The pore volume of the porous carbon is 0.4-0.8 cm 3 / g, preferably 0.55-0.8 cm 3 / g, for example 0.47 cm 3 / g, 0.53 cm 3 / g, 0.54 cm 3 / g, 0.55 cm 3 / g, 0.56 cm 3 / g, 0.57 cm 3 / g, 0.59 cm 3 / g, 0.62 cm 3 / g, 0.64 cm 3 / g, 0.65 cm 3 / g, 0.67 cm 3 / g, 0.68 cm 3 / g, 0.7 cm 3 / g, 0.71 cm 3 / g, 0.72 cm 3 / g or 0.75 cm 3 / g; (7) The micropore ratio of the porous carbon is 40%-75%, preferably 53%-75%, for example, 40.23%, 48.52%, 49.63%, 52.67%, 54.73%, 56.42%, 56.58%, 57.49%, 62.87%, 64.52%, 67.52%, 67.63%, 67.72%, 67.85%, 68.23%, 68.57%, 68.75%, 68.98% or 71.89%; (8) The porous carbon has an average pore size of 1.75-1.85 nm, for example, 1.7713 nm, 1.7781 nm, 1.7808 nm, 1.7816 nm, 1.782 nm, 1.7832 nm, 1.7845 nm, 1.786 nm, 1.7908 nm, 1.7912 nm, 1.7965 nm, 1.7992 nm, 1.8012 nm, 1.802 nm, 1.8027 nm, 1.8107 nm, 1.8161 nm, 1.8171 nm or 1.8313 nm; (9) The tap density of the porous carbon is 0.36-0.45 g / cm 3 , preferably 0.36-0.425 g / cm 3 , for example 0.374 g / cm 3 , 0.381 g / cm 3 , 0.384 g / cm 3 , 0.385 g / cm 3 , 0.386 g / cm 3 , 0.387 g / cm 3 , 0.401g / cm 3 , 0.402 g / cm 3 , 0.407 g / cm 3 , 0.41 g / cm 3 , 0.413 g / cm 3 , 0.416 g / cm 3 , 0.426 g / cm 3 , 0.428 g / cm 3 , 0.43 g / cm 3 , 0.435 g / cm 3 or 0.439 g / cm 3 .
3. A method for preparing porous carbon, characterized in that: It includes the following steps: S1. subjecting a precursor solution to an ionothermal reaction to obtain an ion gel; the precursor solution comprises carbon nanotubes, an ionic liquid, a carbon precursor and a crosslinking agent, the viscosity of the ionic liquid is 0.03-0.35 Pa·s, and the mass ratio of the carbon nanotubes, the ionic liquid, the carbon precursor and the crosslinking agent is (5-10): (25-40): (2-5): (0.2-0.5); S2, freeze-drying the ion gel to obtain a freeze-dried gel; S3, carbonizing the freeze-dried gel.
4. The method for preparing porous carbon according to claim 3, characterized in that: It meets at least one of the following conditions: (1) In step S1, the diameter of the carbon nanotubes is 1-2 nm; (2) In step S1, the length of the carbon nanotube is 0.5-30 μm; preferably, the length of the carbon nanotube is 0.5-2 μm; preferably, the length of the carbon nanotube is 5-30 μm; (3) In step S1, the carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes; preferably, the carbon nanotubes are single-walled carbon nanotubes and multi-walled carbon nanotubes, and the mass ratio of the single-walled carbon nanotubes to the multi-walled carbon nanotubes is (1-6): (1-4), for example, 1:1, 3:1 or 1:3; (4) In step S1, the carbon nanotubes are modified with carboxyl groups; preferably, the carboxyl content of the carbon nanotubes is greater than 2 wt%, for example, 2.73 wt%; (5) In step S1, the viscosity of the ionic liquid is 0.03-0.25 Pa·s, for example, 0.039 Pa·s, 0.118 Pa·s, 0.14 Pa·s, 0.202 Pa·s or 0.341 Pa·s; (6) In step S1, the ionic liquid is an imidazole ionic liquid, such as [EMIM]BF4, [HMIM]BF4, [C7MIM]BF4, [OMIM]BF4 or [BMIM]BF4; (7) In step S1, the carbon precursor is polyvinyl alcohol; (8) In step S1, the precursor solution further includes a surfactant; the surfactant is preferably sodium dodecyl sulfate; the mass ratio of the carbon nanotubes to the surfactant is preferably (0.2-0.3): 0.1, such as 0.2: 0.1, 0.25: 0.1 or 0.3: 0.1; (9) In step S1, the cross-linking agent is glutaraldehyde; (10) In step S1, the mass ratio of the carbon nanotubes to the ionic liquid is (0.2-0.3): 0.8, for example, 0.2: 0.8, 0.25: 0.8 or 0.3: 0.8; (11) In step S1, the mass ratio of the carbon nanotubes to the carbon precursor is (0.2-0.3): 0.07, for example, 0.2: 0.07, 0.25: 0.07 or 0.3: 0.07; (12) In step S1, the mass ratio of the carbon nanotubes to the cross-linking agent is (0.2-0.3): 0.01, for example, 0.2: 0.01, 0.25: 0.01 or 0.3: 0.01; (13) In step S1, the carbon nanotubes are first mixed with the ionic liquid; during the mixing, stirring or ultrasound is preferably used; the stirring speed is preferably 300-800 rpm; the stirring time is preferably 30-90 min; the ultrasound frequency is preferably 20 kHz; the ultrasound power is preferably 500 W; and the ultrasound time is preferably 30 min; (14) In step S1, the temperature of the ion thermal reaction is 150-350°C, for example, 250°C; (15) In step S1, the ion thermal reaction time is 2-24 h, for example 8 h; (16) In step S2, the freeze-drying temperature is -80 to -20°C, for example, -80°C, -50°C or -20°C; (17) In step S2, the freeze-drying time is 2-10 h; (18) In step S3, the atmosphere of the carbonization treatment is a protective gas, such as nitrogen or an inert gas; the flow rate of the protective gas is preferably 3 L / min; (19) In step S3, the end temperature of the carbonization treatment is 600-1000°C, preferably 700-1000°C, for example 600°C, 700°C, 800°C, 900°C or 1000°C; (20) In step S3, the carbonization treatment time is 0.5-2.5 h, preferably 1-2 h, for example 0.5 h, 1 h, 1.5 h, 2 h or 2.5 h; (21) In step S3, the carbonization treatment is as follows: in a nitrogen atmosphere, the heating rate is set to increase the temperature to 400°C at 2°C / min, then increase the temperature to 600°C at 1°C / min, and then increase the temperature to 800°C at 2°C / min, and carbonize for 1 h.
5. A porous carbon obtained by the method for preparing porous carbon as claimed in claim 3 or 4.
6. A silicon-carbon negative electrode material, characterized in that: It includes the porous carbon as described in claim 1, 2 or 5, silicon particles distributed in the pores of the porous carbon and a carbon layer coated on the surface of the porous carbon; based on the total mass of the silicon-carbon negative electrode material, the mass of the porous carbon accounts for 40-70%, the mass of the silicon particles accounts for 10-30%, and the mass of the carbon layer accounts for 0.5-10%.
7. A method for preparing a silicon-carbon negative electrode material, characterized in that: It includes the following steps: Step 1, in a protective atmosphere, at 300-400° C., passing a silicon source gas through the porous carbon as claimed in claim 1, 2 or 5 to obtain a composite material; Step 2, passing a carbon source gas through the composite material at 600-700° C. under a protective atmosphere; Preferably, it satisfies at least one of the following conditions: (1) The protective atmosphere is nitrogen or an inert gas; (2) In step 1, the silicon source gas is SiH4; (3) In step 1, the flow rate of the silicon source gas is 5-10 mL / min; (4) In step 1, the silicon source gas is introduced for 30-60 min; (5) In step 1, the vacuum degree of the protective atmosphere is 10-50 Pa, for example, 20 Pa; (6) In step 2, the carbon source gas is acetylene; (7) In step 2, the amount of the carbon source gas introduced is 2-5 mL / min; (8) In step 2, the carbon source gas is introduced for 60-120 min.
8. A porous carbon obtained by the method for preparing a silicon-carbon negative electrode material as claimed in claim 7.
9. A pole piece, characterized in that: It comprises a coating layer and a current collector, wherein the coating layer comprises the silicon-carbon negative electrode material as claimed in claim 6 or 8.
10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Carbon material as well as preparation method and application thereof
CN115554982A
Cited By
Modified porous carbon, silicon carbon material, preparation method and application of modified porous carbon and silicon carbon material in lithium ion battery
CN120097323A